Experimental Study on Performances of a New Absorption Refrigeration System Driven by Double Low-grade Energy - He Lijuan; Zhu Chaoqun; Yang Bin; Wang Lifang; Zhang Shaohua; Xiao Zhuonan (Zhileng xuebao)
To solve the problem caused by transcritical CO2 compression refrigeration system, a new absorption refrigeration system driven by double low-grade energy was presented based on the principle of energy cascade utilization. Based on mathematical model for each component of the system, an experimental equipment driven by the double low-grade energy were developed. The effect of operating parameters, such as hot source temperature, cooling water inlet temperature and cooled medium, on the system performances had been investigated under constant flow rate. The results showed that the new absorption refrigeration system owned a higher COP and the lowest refrigeration temperature ﹣15.2 ℃ under the same experimental conditions. The study results are helpful to the optimal design.